A case of amblyopia with contralateral optic nerve hypoplasia. (17th January 2013) - Frantz, Kelly A; Pang, Yi
Abstract : We describe an unusual case of unilateral optic nerve hypoplasia (ONH) in a patient with contralateral anisometropic/strabismic amblyopia. A seven‐year‐old boy presented with visual acuities of 6/12 R and 6/18 L and eccentric fixation in the left eye. Cycloplegic retinoscopy was R +1.50/‐0.50 × 180 and L +5.25 DS. Funduscopy revealed optic nerve hypoplasia of the right eye. The patient fixated with his better‐seeing right eye, despite the optic nerve hypoplasia. His reduced vision may be attributed to optic nerve hypoplasia in the right eye and amblyopia in the left. Although optic nerve hypoplasia can occur with ipsilateral amblyopia, we believe this is the first reported case of unilateral optic nerve hypoplasia in the fellow eye of an amblyopic patient.